Construction of nptII–mtsfGFP fusion gene construct by overlap extension PCR - Cheng, Yang Yan (2025)
In plant transformation, the Agrobacterium-mediated system (AMT) is widely used due to deliver transgenes into multi-layered plant cells without causing damage. Previously, the GatewayTM-compatible binary vectors, pG103 and pG104 were built to enable convenient transgene insertion. For the selection of transformed cells, plasmid vectors pG103 and pG104 harbor the selectable markers neomycin phosphotransferase II (NptII) and mitochondrial recoded neomycin phosphotransferase II (mtNptII) genes, respectively, which confer resistance to aminoglycoside antibiotics for nuclear and mitochondrial transformation. To facilitate visualization of the protein expression of the gene of interest (GOI), a reporter gene is often translationally fused it. The green fluorescent protein (GFP) gene is widely used as a reporter gene. This project used mitochondrial recoded superfolder GFP (mtsfGFP) gene, which encode the same superfolder GFP protein, is designed for expression in either the host’s nucleus and mitochondria. This project aimed to fuse the NptII and mtNptII with mtsfGFP using overlap extension PCR (OE-PCR). A 3-step OE-PCR approach using megaprimers was employed. However, due to the formation of secondary structures of the megaprimer during the PCR reaction, non-specific amplicons were generated. To eliminate these non-specific amplicons and obtain the desired amplicons, parameters such as primer and template DNA concentrations, number of thermal cycles, and annealing temperature, were performed for each step of the OE-PCR. Consequently, amplicons carrying the NptII- mtsfGFP and mtNptII- mtsfGFP fusion genes were successfully generated. In the future, these amplicons will be cloned into the Agrobacterium binary vectors for host transformation. They will facilitate qualitative and quantitative analysis of transgenes in the host’s nucleus and mitochondria.